Duodenal Organoids From Metabolic Dysfunction-Associated Steatohepatitis Patients Exhibit Absorptive and Barrier Alterations - Alia Hadefi; Morgane Leprovots; Gilles Dinsart; Maryam Marefati; Marjorie Vermeersch; Daniel Monteyne; David Pérez-Morga; Anne Lefort; Frédérick Libert; Laurine Verset; Claire Liefferinckx; Christophe Moreno; et al. (Gastro Hep Advances)
Background and Aims: Metabolic dysfunction-associated steatohepatitis (MASH) is a progressive liver disease that can lead to fibrosis, cirrhosis, and hepatocellular carcinoma. Though MASH is closely tied to metabolic risk factors, the underlying pathogenic mechanisms remain scarcely understood. Recent research has emphasized the importance of the gut-liver axis in its pathogenesis, an aspect less explored in human studies. Here, we investigated whether the duodenal epithelium of MASH patients could exhibit intrinsic dysfunctions. Methods: Duodenal epithelial organoids were generated from 16 MASH patients and 14 healthy controls. Biopsies and patient-derived organoid transcriptomes were then analyzed to evaluate if specific intestinal pathways were differentially modulated in MASH subjects. Functional assays were performed to assess the duodenal epithelial absorptive potential and barrier functionality. Results: Organoid formation efficiency was similar between control-derived duodenal epithelial organoids and MASH-derived duodenal epithelial organoids (MDEOs) (71% and 69%, respectively). Despite global heterogeneity in growth patterns, MDEOs frequently exhibited cystic spheroid morphology. MDEOs displayed altered digestive potential associated with reduced mature absorptive cell fate, but they retained their lipid metabolic capacity, possibly mediated by lipid oxidation in stem/progenitor cells. Additionally, MDEOs misexpressed components of tight and adherens junctions and desmosomes compared to controls. However, MDEOs maintained pore and leak pathway integrity, indicating that the duodenal epithelial barrier remained functionally preserved under tested conditions. Conclusion: This study provides evidence that the duodenal epithelium of MASH patients exhibits significant alterations in its nutrition-related and barrier functions. This study sheds light on the intricate dynamics of duodenal epithelial alterations in MASH, highlighting potential therapeutic avenues for restoring intestinal functions.